Optimization of Digital Technology to Encourage Sustainable Halal Tourism in Lon Malang Beach Sampang Regency - Al Mursyid, Mohammad Irsyad; Hermawan, Rudi; Rosyiidah, Afiifah Al (Universitas Trunojoyo Madura, 2024)
Lon Malang Beach in Sampang Regency has great potential as a sustainable halal tourism destination. However, the management and promotion of this destination still faces challenges, especially in utilizing digital technology to support the growth of this sector. This research aims to analyze the role of digital technology in optimizing halal tourism, including promotion, service and destination management. Research methods involve literature analysis, interviews, and field observations. The research results show that the use of digital technology such as social media, map-based applications and online reservation platforms can increase the visibility and accessibility of destinations. Providing information regarding halal facilities is also a key factor in attracting Muslim tourists. This optimization is expected to be able to support economic, social and environmental sustainability in the area. Some of the important aspects that have been implemented include internet connectivity through Wifi facilities, tourism information systems that utilize social media and websites, QRIS-based payment systems, and local community empowerment through digital skills training and debriefing. Although there have been efforts to optimize digital technology, its implementation still faces several obstacles, such as low digital understanding among the public and challenges in creating attractive digital content.